Analisis Kelayakan Penerima BLT (Bantuan Langsung Tunai) Menggunakan Metode Logistic Regression - Ira Zulfa; Salmandi Futra; Mahdalena Mahdalena (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
The distribution of Direct Cash Assistance (BLT) in Pedekok Village, Pegasing District, Central Aceh Regency, is still carried out manually through village deliberations, so that it often causes subjectivity and inaccuracy of targets. This study aims to objectively analyze the feasibility of BLT recipients using the Python-based Logistic Regression method. The type of research used is applied quantitative research with a total of 166 Family Cards data covering economic and social variables such as income, number of dependents, elderly status, people with disabilities, and chronic diseases. The research process includes the pre-processing stages of data, variable coding, model formation, and performance evaluation using accuracy, precision, recall, and confusion matrix metrics. The results of the analysis showed that the Logistic Regression method was able to provide an accuracy level of 97% in the classification of BLT recipients. Income factors, the existence of members with disabilities, and chronic diseases are the variables that have the most influence on the probability of eligibility for receiving assistance. The implementation of this method is expected to increase transparency, objectivity, and accountability in the process of determining BLT recipients at the village level.